Literature Review: Inquiry Social Complexity-STEAM Model Based on Math Trail-Virtual Reality Activity Nuanced with Javanese Culture in Improving Critical Thinking Ability - Suryonegoro, Bayu Murti; Wuryastuti, Monica Luishanda; Dewi, Nuriana Rachmani (Journal Evaluation in Education (JEE), 2024)
Purpose of the study: Analyse various literature studies on the Inquiry Social Complexity-STEAM model based on Math Trail-Virtual Reality activities with Javanese cultural nuances in improving students' critical thinking skills. Methodology: This research method uses a literature review. Researchers look for data from books, journals, or relevant research articles and include them in the findings and discussion section to reach a conclusion. This research uses descriptive qualitative data analysis techniques to study literature by describing the results of sources obtained either through books, journals, or related research articles. Main Findings: The syntax of inquiry social complexity STEAM learning model based on math trail virtual reality activities with Javanese cultural nuances can be concluded that each syntax encourages students to find, investigate, construct, and integrate the knowledge gained to form better critical thinking skills by accommodating all aspects of students' abilities with different levels to participate in every aspect and step of learning. Novelty/Originality of this study: The addition of the STEAM approach, especially in the Inquiry Social Complexity Learning model, and math trail-based activities using virtual reality technology that has never been done before or integrated into a maths classroom.